2021
DOI: 10.1039/d1fo00650a
|View full text |Cite
|
Sign up to set email alerts
|

Edible mushroom consumption and incident hyperuricemia: results from the TCLSIH cohort study

Abstract: Background: Basic studies have found that xanthine oxidase inhibitor extracted from mushrooms has inhibitory effects on hyperuricemia. However, the association between mushroom consumption and hyperuricemia is unknown in humans. Objective:...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Another recent meta‐analysis of prospective studies found that mushroom consumption was associated with a lower risk of all‐cause mortality [54]. A very recent prospective cohort study of nearly 20 000 participants found for the first time that higher mushroom consumption was significantly associated with lower incidence of hyperuricemia, which may play an important role in the prevention of hypertension [55]. These findings provide more robust evidence about the potential health benefits of mushrooms.…”
Section: Ergothioneine Consumption and Health Outcomesmentioning
confidence: 98%
“…Another recent meta‐analysis of prospective studies found that mushroom consumption was associated with a lower risk of all‐cause mortality [54]. A very recent prospective cohort study of nearly 20 000 participants found for the first time that higher mushroom consumption was significantly associated with lower incidence of hyperuricemia, which may play an important role in the prevention of hypertension [55]. These findings provide more robust evidence about the potential health benefits of mushrooms.…”
Section: Ergothioneine Consumption and Health Outcomesmentioning
confidence: 98%
“…38,39 These studies suggested that mitigation of the risk of MCI may be attributed to the composition of protective effects of various nutrients from mushrooms. Accumulating evidence also hinted that mushroom intake was associated with reduced risks of depression 40 and lipid dysfunction, 41,42 and the improvement in mental and metabolic health may delay the cognitive decline. 43,44…”
Section: Food and Function Papermentioning
confidence: 99%
“…In the continuous NHANES 2007-2018, serum UA was measured on a Beckman Synchron LX20 using an automated colorimetric method, which had been validated against a uricase assay [33]. Based on a previous study, hyperuricemia was defined in this study as serum UA levels > 420 μmol/L in men and > 350 μmol/L in women [21].…”
Section: Ascertainment Of Hyperuricemiamentioning
confidence: 99%
“…A previous study using an animal model demonstrated that intervention with xanthine inhibitors extracted from oyster mushroom fruiting bodies reduced serum urate levels [20]. Additionally, a recent cohort study conducted in China showed that mushroom consumption was associated with a lower risk of incident hyperuricemia [21]. To the best of our knowledge, apart from the previously mentioned Chinese study, there are no other prospective studies with long-term follow-up based on communitybased populations that have explored the association between mushroom consumption and the risk of hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%